Rape or Seduction? - Ignatia Maria Hendrarti (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2017)
AbstractThis paper deals with the description of many kinds depictions of rape in Indonesian women popular fiction. First, the problematic interpretation of rape shows that many people, especially those working in legal institution, have spesific male interpretation of rape. Some feminists expose that rape, as defined in legal context, fail to determine whether a sexual affair is rape or not. The difficulty also lies in who is in a position to interpret the meaning of such sexual affair. In other words, the notion of who is looking at the case is very crucial. The 'truth' about rape depends on who interprets the situation. In the context of literary depiction of rape, the analysis shows that many women writers are reluctant to give clear picture of rape. Therefore, many “rape” incidents will tend to be interpreted as just a common sexual affair.Keywords:Feminist Criticism, popular literature, politics